A Victorian Embarrassment: Consular Jurisdiction and the Evils of Extraterritoriality - Cobbing, Andrew (International history review, 2018)
In 1856, the Treaty of Paris nominally welcomed the Ottoman Empire into the Concert of Europe, but this exposed a deep fault line in international relations. Although the gesture implied full sovereign rights, it seemed incompatible with the extraterritorial privileges held by Europeans in Ottoman lands under the age-old capitulations. New commercial treaties complicated the issue by extending similar privileges to British subjects as far afield as China, Siam and Japan. Consular jurisdiction soon became the focus of controversy in Westminster as extraterritoriality featured prominently in local disputes following British commercial expansion across Asia, among them the Arrow incident that led to the Second Opium War. In Japan and other states, it would also become a key grievance in popular campaigns against 'unequal treaties' and the injustices of informal empire. This analysis shows how, even before such narratives of resistance emerged, there was already a seam of ambivalence in Victorian political discourse on the question of extraterritoriality. In the Foreign Office, it came as no surprise to be told of defects in these treaties, but it was the context of the existing debate, notably fresh initiatives to set up mixed courts, that framed the British response.